Safety and efficacy of restarting antiplatelet therapy after intracerebral hemorrhage - Eun, Mi-Yeon; Jung, Jin-Man (Annals of Translational Medicine, 2019)
Intracerebral hemorrhage (ICH) develops as a result of bleeding from a small arterial rupture and can be included in the category of cerebral small vessel disease (1,2). Because the risk factors for ICH such as advanced age, hypertension, and cigarette smoking are also those for occlusive vascular diseases (3), many ICH patients have an accompanying ischemic stroke or coronary artery disease, which are significant causes of long-term morbidity and mortality in these cases (4-6). Hence, life-long antithrombotic therapy may be required in a considerable number of patients to prevent or/and treat occlusive vascular diseases even after ICH.